Second primary malignancy of oral mucosa: a case report - Zielińska-Kaźmierska, Bogna; Neskoromna, Aneta (Contemporary Oncology/Współczesna Onkologia, 2004)
Oral mucosal multiple SPTs are rarely presented in the literature. These tumors have been more closely observed in medical case reports in the last 20 years. A modern definition of SPT was developed by the International Agency for Research on Cancer (IARC) in 1991. Three conditions should be fulfilled to diagnose SPT: (a) both tumors must be confirmed histopathologically, (b) both tumors must be localized separately, and (c) metastatic condition of the second tumor must be excluded. There are two different types of SPT: a simultaneous one and metachronous one. The frequency of SPTs in the head and neck region is 9-36%, and is still increasing. Paradoxically, that frequency is growing together with the elongation of the follow-up post-op period of the primary lesion. The authors present the case treated at the Department of Cranio-Maxillofacial Surgery of the Medical University of Łódź, in which three years after the ablation of oral mucosa planoepithelial cancer in the left buccal region, the second lesion of the same cancer was diagnosed in the opposite buccal region. The dynamics of the second lesion was greater than of the first one, and local infiltration was more aggressive. The case fulfilled all criteria of metachronous SPT diagnosis. The authors present diagnostic and treatment problems resulting from the dynamics of the disease process.